Strategi Optimalisasi Waktu Pendidikan Jasmani Di Sekolah Berdasarkan Pedoman Kesehatan Nasional: Studi Kualitatif Di Sekolah Dasar Negeri 2 Jeumpa Bireuen - Saputra, Dedi; Alyadi S; Masyitah; Hidayat, Rahmad; Arkan , Muhammad (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2024)
Physical education plays a crucial role in supporting the health and fitness of elementary school students. According to national health guidelines, each student is recommended to engage in at least 150 minutes of physical activity per week. This study aims to analyze strategies for optimizing physical education time at SD Negeri 2 Jeumpa, located in the suburban area of Bireuen. A qualitative approach with a case study design was used, involving the school principal, physical education teachers, and parents. Data were collected through interviews and direct observation. The results show that the main challenges in optimizing physical education time are limited sports facilities, a packed curriculum, and lack of parental support. Several strategies that can be implemented include schedule adjustments, maximizing available facilities, and fostering closer collaboration between the school, parents, and the community. This study suggests the importance of stronger cooperation to enhance the quality of physical education.